2018
DOI: 10.1111/ors.12365
|View full text |Cite
|
Sign up to set email alerts
|

Nasolabial cyst: a case report

Abstract: Nasolabial cysts are rare non-odontogenic cysts of soft tissue that usually present as asymptomatic swellings beneath the ala of the nose. Their pathogenesis is uncertain. The presence of the lesion is perceived clinically and by the aid of radiological imaging. The usual treatment is surgical excision. Nasolabial cysts, when infected, are painful and mistreated occasionally as odontogenic defects. This article reports a case of a nasolabial cyst that was initially diagnosed and treated as a periapical abscess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(46 reference statements)
0
1
0
2
Order By: Relevance
“…Excluding endoscopic marsupialization and complete surgical excision, all the other modalities have a high recurrence rate [8,13]. Sheikh et al reviewed 79 articles with 311 patients with a nasolabial cyst and reported no significant recurrence rate found between the sublabial and transnasal marsupialization excision [18,19]. Nearly in all published literature, complete surgical excision described as the best treatment for the nasolabial cyst [6,13].…”
Section: Discussionmentioning
confidence: 99%
“…Excluding endoscopic marsupialization and complete surgical excision, all the other modalities have a high recurrence rate [8,13]. Sheikh et al reviewed 79 articles with 311 patients with a nasolabial cyst and reported no significant recurrence rate found between the sublabial and transnasal marsupialization excision [18,19]. Nearly in all published literature, complete surgical excision described as the best treatment for the nasolabial cyst [6,13].…”
Section: Discussionmentioning
confidence: 99%
“…Os CNLs representam cerca de 0,7% de todos os cistos da região maxilofacial e 2,5% dos cistos não odontogênicos (BOFFANO et al, 2011;PEREIRA FILHO et al, 2002;ZOGRAFOS et al, 2018). Estas lesões são geralmente unilaterais, mas estima-se que aproximadamente 10% dos casos sejam bilaterais.…”
Section: Discussionunclassified
“…Os cistos nasolabiais (CNL) são lesões incomuns, benignas, de tecido mole, não-odontogênicas, (BOFFANO et al, 2011;OCAK et al, 2017) localizadas na região paramediana da maxila e abaixo da asa nasal (FRIEDRICH et al, 2012;PEREIRA FILHO et al, 2002) descritos primeiramente por Zuckerlandl, em 1882 (ACAR et al, 2014;CHINELLATO et al, 1984;ZOGRAFOS et al, 2018). A patogênese dos CNL é incerta.…”
unclassified